Exercise Training Is Associated With Treatment Response in Liver Fat Content by Magnetic Resonance Imaging Independent of Clinically Significant Body Weight Loss in Patients With Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Stine, Jonathan G.; DiJoseph, Kara; Pattison, Zach; Harrington, Alex; Chinchilli, Vernon M.; Schmitz, Kathryn H.; Loomba, Rohit (The American journal of gastroenterology, 2023)
Exercise training is crucial in the management of nonalcoholic fatty liver disease (NAFLD); however, whether it can achieve clinically meaningful improvement in liver fat is unclear. We investigated the association between exercise training and the achievement of validated thresholds of MRI-measured treatment response. Randomized controlled trials in adults with NAFLD were identified through March 2022. Exercise training was compared with no exercise training. The primary outcome was ≥30% relative reduction in MRI-measured liver fat (threshold required for histologic improvement in nonalcoholic steatohepatitis activity, nonalcoholic steatohepatitis resolution, and liver fibrosis stage). Different exercise doses were compared. Fourteen studies (551 subjects) met inclusion criteria (mean age 53.3 yrs; body mass index 31.1 kg/m 2 ). Exercise training subjects were more likely to achieve ≥30% relative reduction in MRI-measured liver fat (odds ratio 3.51, 95% confidence interval 1.49-8.23, P = 0.004) than those in the control condition. An exercise dose of ≥750 metabolic equivalents of task min/wk (e.g., 150 min/wk of brisk walking) resulted in significant treatment response (MRI response odds ratio 3.73, 95% confidence interval 1.34-10.41, P = 0.010), but lesser doses of exercise did not. Treatment response was independent of clinically significant body weight loss (>5%). Independent of weight loss, exercise training is 3 and a half times more likely to achieve clinically meaningful treatment response in MRI-measured liver fat compared with standard clinical care. An exercise dose of at least 750 metabolic equivalents of task-min/wk seems required to achieve treatment response. These results further support the weight-neutral benefit of exercise in all patients with NAFLD.